A participatory e-planning model in the urban renewal of China: Implications of technologies in facilitating planning participation. (February 2023) - Tian, Li; Liu, Jinxuan; Liang, Yinlong; Wu, Yaxin
While collaborative planning has gained popularity in addressing conflicts of interest in urban renewal, the development of information communication technologies has provided creative tools in participatory planning. To accommodate the needs of participatory e-planning, we designed a digital collaborative platform composed of four modules to establish a framework for all stakeholders to participate in the urban renewal process in China. By taking a village as a case study (hereafter referred to as village X ), this research introduces the application of a digital platform in the renewal of an old village facilitated by a third party. Although the application of e-planning participation in the renewal of X village has been effective, its further application has encountered challenges, such as willingness, the capacity of the residents, and credibility, due to the lack of an institutionalized arrangement. Compared with the West, China has a long way to go in promoting public participation in urban renewal through institutional arrangements. Educating the public and deepening the understanding of local governments in the necessity of public participation should be the future task of urban planners in China. The limitations and further applications of digital platforms are also discussed.